Knockdown of TRPV Genes Affects the Locomotion and Feeding Behavior of Nilaparvata lugens (Hemiptera: Delphacidae). Issue 1 (15th February 2020) - Zhu, Jinghua; Liu, Xiaoqing; Zhu, Kunmiao; Zhou, Hanyu; Li, Liang; Li, Zengxin; Qin, Weiwei; He, Yueping
Abstract: The vanilloid-type transient receptor potential (TRPV) channel is reported to be the molecular target of the commercial insecticide pymetrozine, which specifically disrupts the feeding of plant sap-sucking insects. However, the functions of TRPV channels in plant sap-sucking insects have not been fully elucidated. In the present study, RNA interference was used to investigate the effects of the knockdown of TRPV genes ( Nan and Iav ) on the mortality, locomotion, and feeding behavior of an important plant-feeding insect pest in rice, the brown planthopper, Nilaparvata lugens . Injecting dsRNA of Nan and Iav into fourth-instar nymphs significantly knocked down the target genes. The injection of ds Nan or ds Iav did not affect any morphological phenotype (including leg extension) of N. lugens nymphs and adults. Knockdown of Nan or Iav resulted in significantly decreased climbing activity against top plants but did not influence the leg-griping strength of adults. Knockdown of Nan resulted in a significantly elevated mortality of N. lugens in the observation period of 7 d after injection, whereas no significant difference in survival rates 7 d after injection was found between ds Iav -injected and ds GFP -injected insects. Electropenetrographic (EPG) recordings indicated that knockdown of Nan and Iav reduced the ingestion activity in the rice phloem tissues of N. lugens . Knockdown of Nan and Iav significantly reduced the amount of honeydew excreted by N. lugens . Our findings indicated a relationship between TRPV and N. lugens locomotion and feeding behavior, which may help to fully elucidate the functions of TRPV in insects.